Incidence of Venous Thromboembolism Following TAA: Does Chemoprophylaxis Work?. Issue 4 (November 2022) - Martinazzi, Brandon J.; Nam, Hannah; Dopke, Kelly; Mansfield, Kirsten N.; Koroneos, Zachary; Ptasinski, Anna; Manto, Kristen; Kirchner, Gregory; Aynardi, Michael C.
Category: Ankle Arthritis; Ankle; Other Introduction/Purpose: Venous thromboembolism is a devastating and costly complication following TAA. The true incidence of VTE is unknown and the decision to prescribe chemoprophylaxis in foot and ankle surgery continues to be debated. At our institution, all patients receive a four-week course of chemoprophylaxis following TAA. The purpose of this study was to evaluate the incidence of VTE at our institution in patients receiving routine chemoprophylaxis. Methods: Following institutional board approval, a retrospective chart review was conducted for all patients that underwent TAA from 2018-2021 by a single surgeon. Patients were followed from the time of surgery to their six-week follow-up. Demographics and the type of chemoprophylaxis was recorded. For comparison, a large online database was queried using ICD and CTP codes in order to determine the incidence of VTE at 2 week and 6 weeks postoperatively for patients that underwent TAA and did not receive any form of chemoprophylaxis. Results: At our institution, from 2018-2021, 56 patients underwent TAA. The mean age of our cohort was 60.9 (Range, 56-83). In our cohort, 31 patients were male, 25 were female, and the mean patient BMI was 33.8 (Range, 21-56.2). Of the 56 patients, 12 received aspirin (81 mg), 25 received aspirin (325 mg), 16 received enoxaparin (40 mg), 2 received apixaban (5 mg), and 1 received rivaroxaban (20 mg). The total incidence of VTE at 6 weeks was 0%. For comparison, using a large online database (from 2011- 2021), 1, 463 patients underwent TAA and did not receive postoperative chemoprophylaxis. Of these patients, 13 (0.89%) developed a postoperative VTE at 6-weeks following surgery. Conclusion: At our institution, the rate of VTE at 6-weeks postoperatively was 0%. This was lower than a large online database rate (0.89%) in patients that did not receive chemoprophylaxis. Further investigation is needed.